2014
DOI: 10.1051/sfn/20141302002
|View full text |Cite
|
Sign up to set email alerts
|

Polarized neutron diffraction

Abstract: Abstract. This lecture addresses the different applications of polarized neutron diffraction, with or without subsequent polarization analysis, to the determination of magnetic structures, to the separation of magnetic and nuclear contributions and to magnetization distributions mapping. The first sections introduce some of the fundamental equations. Then the problems of magnetic domains, encountered in crystals and of particular importance as soon as polarized neutrons are concerned, are presented. The final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Gukasov and Brown showed that, at sufficiently low external magnetic field strengths at which the material exhibits a linear magnetic response, the magnetic structure factor can be modeled by introducing a susceptibility tensor for each distinct crystallographic site occupied by a magnetic atom . In this approach, measured PND flipping ratios are used to fit atomic magnetic susceptibility tensors for each of the individual magnetic atoms in the asymmetric unit, provided that the nuclear structure factors are known from a complementary structural study . The magnetic structure factor in this model has the form [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Gukasov and Brown showed that, at sufficiently low external magnetic field strengths at which the material exhibits a linear magnetic response, the magnetic structure factor can be modeled by introducing a susceptibility tensor for each distinct crystallographic site occupied by a magnetic atom . In this approach, measured PND flipping ratios are used to fit atomic magnetic susceptibility tensors for each of the individual magnetic atoms in the asymmetric unit, provided that the nuclear structure factors are known from a complementary structural study . The magnetic structure factor in this model has the form [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the anisotropy of the dynamical structure factor near Dirac points may serve as a signal of the anisotropic Dirac dispersion. The information about the vector chiral order of the spin liquid may be revealed in nuclear-magnetic interferences in the chiral magnetic scattering [46][47][48] of an initially unpolarized neutron beam.…”
Section: Discussion and Estimatesmentioning
confidence: 99%
“…Polarized neutrons enhance the sensitivity to the magnetic scattering, which for molecular crystals is generally weak compared to the nuclear scattering that is the primary contribution to the diffraction pattern. 42 The intensity of magnetic scattering observed in a Bragg peak is proportional to the magnetic structure factor, which can be written as 37…”
Section: Single-crystal Polarized Neutron Diffractionmentioning
confidence: 99%